KESESUAIAN SARANA DAN PRASARANA WISATA PANTAI JIKUMERASA DI DESA JIKUMERASA KABUPATEN BURU - Kesya Pattimukay; Yofita Anaktototy; Margie Wattimury (Universitas Pattimura, 2023)
Jikumerasa Beach or known as Djiku Beach is one of the most popular and visited natural tourist attractions on Buru Island. The purpose of this study is to review the suitability of the completeness of facilities and infrastructure of tourist attractions based on the standards of suitability of the completeness of facilities and infrastructure proposed by Lothar and Kreck in Yoeti (2006). The standard of completeness of facilities and infrastructure proposed by Lothar and Kreck, among others, from the facility facilities are divided into basic facilities and completeness of tourism facilities, while in terms of infrastructure facilities consist of general economic infrastructure, and general social infrastructure. Completeness of tourist facilities and infrastructure is a very important factor to support the comfort of tourists in carrying out tourism activities. This is the background for the author to conduct a review of the facilities and infrastructure located on Djiku beach to see the suitability of the completeness of these facilities and infrastructure. The method used is a qualitative method with field observation techniques and literature studies to obtain references and descriptions related to ideal facilities and infrastructure in tourism. The conclusion of this research is that the completeness of the facilities and infrastructure of Djiku beach tourist attractions is identified as quite complete and feasible. The results of this study are expected to be able to become a reference for tourism development in the area.